Effects of Coffee Intake and Intraperitoneal Caffeine on Bone Repair Process - A Histologic and Histometric Study - Macedo,Rander Moreira (2015)
Studies have suggested that caffeine acts on bone promoting an increase of calcium excretion, inhibition of osteoblast proliferation and delay in tissue repair process, raising the risk of fractures, osteoporosis, periodontal disease and affecting the success of bone reconstructive procedures. The aim of this study was to analyze histomorphometrically the process of alveolar bone healing after tooth extraction in rats subjected to daily intake of boiled coffee or intraperitoneal administration of caffeine. Forty-five male rats were divided according to the treatment in Control group (C); Coffee group (CO) - treated with coffee since birth; and Caffeine (CAF) - intraperitoneal injection of aqueous solution of caffeine 1.5% (0.2 mL/100g body weight) for 30 days. When weighing between 250-300 g they were anesthetized, subjected to extraction of the maxillary right incisor, and euthanized 7, 21 and 42 days after surgery for histological assessments of bone volume and the quality of formed bone in the dental socket. The qualitative results demonstrated larger amounts of blood clot and immature bone in animals under treatment of pure caffeine compared to coffee and control. Histometric analysis revealed that coffee treatment led to a 40% drop in bone formation, and caffeine a 60% drop in comparison to control animals (ANOVA p≤0.01). It was concluded that both the daily ingestion of coffee and the intraperitoneal administration of caffeine in rats delayed the alveolar bone reparative process after tooth extraction, and this effect was more aggressive when pure caffeine was used.